ISSUES OF IMPROVING THE CALCULATION OF THE ZERO RATE OF VALUE ADDED TAX - Djalilov, Rakhmonkul Khamidovich (THE INNOVATION ECONOMY, 2024)
This article examines the impact of the policy implemented in the tax sphere in the digital economy in the tax system on the mechanisms for accounting for value added tax